2000
DOI: 10.1136/ewjm.173.1.33
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of treatment of settling problems and night waking in young children

Abstract: ⅷ Objective To assess the efficacy of treatment of settling problems and night waking in young children. ⅷ Design A systematic review of randomized controlled trials of interventions. ⅷ Setting Electronic bibliographic databases and references on identified papers, hand searches, and personal contact with specialists. ⅷ Subjects Children aged 5 years or younger who had established settling problems or night waking. ⅷ Interventions Interventions had to be described and a placebo, waiting list, or another interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…In addition, parental response about the usefulness and satisfaction with the written material was positive in both studies (Eckerberg, 2002;Kerr et al, 1996). Moreover, Ramchandani et al (2000) found that additional support through telephone calls did not significantly affect health education about sleep behavior techniques through written material. Overall positive results were seen regardless of how the information was delivered.…”
Section: Health Educationmentioning
confidence: 87%
See 2 more Smart Citations
“…In addition, parental response about the usefulness and satisfaction with the written material was positive in both studies (Eckerberg, 2002;Kerr et al, 1996). Moreover, Ramchandani et al (2000) found that additional support through telephone calls did not significantly affect health education about sleep behavior techniques through written material. Overall positive results were seen regardless of how the information was delivered.…”
Section: Health Educationmentioning
confidence: 87%
“…For example, if a child is throwing a tantrum at bedtime in his or her room, the parent does not enter the room. At the end of the interval, the parent briefly enters (i.e., b 15 s) and before leaving provides the child with verbal reassurance (Ramchandani et al, 2000). In their systematic review, Ramchandani et al (2000) assert that interventions that utilized graduated extinction resulted in decreased night awakenings per week.…”
Section: Graduated Extinction and Parental Presencementioning
confidence: 99%
See 1 more Smart Citation
“…However, different families prefer different sleep management approaches (Hiscock et al, 2008;Ramchandani, Webb, & Stores, 2000), with most parents preferring to remain present during infants' transition to sleep and interested in a gentle approach if it is optional (Galland & Mitchell, 2010).…”
Section: Understanding Infant Sleep Patternsmentioning
confidence: 99%
“…They also tend to persist until later childhood if untreated (7,8). Training a child to fall asleep without parental intervention can solve these sleep problems according to two recent meta-analyses of all the published treatment studies (11,12).…”
mentioning
confidence: 99%